Estudio del ingreso familiar promedio y su incidencia en la canasta familiar básica, en la zona urbana del cantón la Mana, en familias de 4 a 6 integrantes, durante el periodo de enero a diciembre del 2012. - Viteri Macías, Carmen Beatriz (2013)
The research entitled “Study of familiar middle income and its incidence in the familiar basic basket, in the urban zone of the Mana canton, in families of 4 to 6 members, during the period from January to December of 2012”, it was placed of performanced in the canton previous mentioned. It has 23.775 habitants (urban zone), according at last census of population and housing made for INEC (Instituto Nacional de Estadísticas y Censos). The elaboration of present study permit identify the impact of familiar middle income, in the familiar basic basket, from urban zone of the Mana canton, it contributes the knowledge of the distribution of salary monthly during 2012, such us the inappropriate use of it. Additionally it establishes the negative factors and repercussions of familiar income inadequate or bad used, to the acquisition the products of the familiar basic basket, for this reason elaborate the survey based in the problematic to research. By means of the research made, it found that 32% of the surveyed families perceived an monthly middle income of 400 dollars, that correspond to be lower to cost of familiar basic basket, it was $587,86 in 2012 (PICTURE 5). Moreover the families indicated in 80.17%, that monthly income was not enough to acquisition the products of the familiar basic basket (PICTURE 6). Based in the bad distribution of salary monthly, it was used to credits and debts in 48%, alcoholic drinks in 16%, fighting cock in 9%, and others reasons. At the last place, the lack of a familiar middle income appropriated, caused in 39% familiar problems, 19% nutritional problems, and in 7% migration of one or some members of La Mana homes.